Developing Intercultural Competence in Future Student Affairs Professionals through a Graduate Student Global Study Course to Doha, Qatar - Haber, Paige; Getz, Cheryl (Catholic Education: A Journal of Inquiry and Practice, 2011)
This paper describes a 2-week global study course to Doha, Qatar for graduate students in the higher education leadership and student affairs program at the University of San Diego. The course sought to develop intercultural competence with a specific focus on understanding Qatari and Middle Eastern perspectives and culture, understanding the unique challenges in higher education student affairs for Qatar and other Middle Eastern countries, and identifying ways for students to apply learning from the course to student affairs practice. These learning outcomes are discussed in the context of the profession of student affairs and the University of San Diego and its Catholic mission. An overview of the global course components is presented along with student and instructor reflections of learning from the course. Challenges from the course are discussed followed by recommendations for similar global study courses.